ANTHROPOLOGICAL CRISIS AND MODERN NET GENERATIONS - Sugrobova, Julia; Karpova, Irina; Dorofei, Yulia; Kaushliyev, Gennadiy (Revista Inclusiones, 2020)
The relevance of the study is due to the escalation of the anthropological crisis caused by the transition of humanity into a new worldview stage of post-industrial and information development, which led to globalization and the humanitarian revolution. In this regard the paper is aimed at identifying the causes and parameters of the anthropological crisis; its philosophical-anthropological and culturological comprehension; definition of characteristics and life strategies of modern net generations of Millennials and Centennials. The main methods of research are the socio-historical and historical-philosophical analysis, and system analysis of social institutions and cultural forms allowing a comprehensive study of the problems of the anthropological crisis.